Detecting Earnings Management: A Foreign Exchange Losses (FEL) Model - Christiawan, Yulius Jogi; Rahmiati, Alfa (Universitas Airlangga, 2017)
Foreign exchange losess bear some pressures for numerous companies in Indonesia particularly for those having liabilities denominated in foreign currencies. This occurs when Indonesian Rupiah (IDR) current exchange rate has weakened against foreign currencies. Related to those phenomenon, this study aims to investigate model earnings management actions using foreign exchange losses (FEL) which provides a method for the detection of earnings management. By employing a quantitative approach, this study used secondary data of financial statements. The data were collected from 50 companies with the largest market capitalisation, 50 of the most active companies based on trading volume, 50 of the most active companies based on the value of trade and 50 of the most active companies by frequency trading. Totally, 200 public companies listed in Indonesia Stock Exchange were gained as the data based on IDX statistical report 2013. The results identify that FEL model is capable to detect earnings management from a transaction in foreign exchange losses. However, the model cannot capture the phenomenon of earnings management if the company does not own or reported long-term debt and profit/loss on foreign exchange. To prove whether the manager will perform earnings management from FEL, it is suggested to conduct further research using the hypothesis of positive accounting theory (PAT)